The effect of physical therapy rehabilitation on fatigue and pain in female patients with fibromyalgia - Gamal Abdelaziz, Nada; Gehan Mahmoud Ramzy; Lotfy Fayed, Hala; Sara M. Ahmed; Mousa Ahmed, Gehan (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
This study aimed to examine the impact of physical therapy rehabilitation program on fatigue, pain and quality of life in female patients with fibromyalgia. It was designed as a single-blinded, randomized, pre and post-test controlled trial. Eighty female patients, aged 25 to 45, diagnosed with fibromyalgia were selected from the Kasr Al Ainy rheumatology outpatient clinic. The participants were allocated into two equal groups using a randomization procedure. Group (A) (control group, n=40) received transcutaneous electric nerve stimulation (TENS), moist heat, core muscle retraining, and manual therapy for trigger points, 3 times/week, for 4 weeks. Group (B) (study group, n=40) received the same treatments as Group A, plus aerobic exercises, flexibility exercises, and cognitive behavioural therapy (CBT), 3 times/week, for 4 weeks. Both groups were assessed before and after treatment using the Fatigue Severity Scale (FSS) and the Fibromyalgia Impact Questionnaire (FIQ). Statistically significant improvements were observed in FSS and FIQ scores for both groups post-treatment (p<0.05). When the two groups were compared after therapy, the study group (B) showed significantly greater improvement in FSS and FIQ (p<0.05). These findings suggest that physical therapy rehabilitation can effectively reduce fatigue, pain, and improve the quality of life for women with fibromyalgia.